forage systems mixed with forage legumes grazed by lactating cows - Clair Jorge Olivo; Michelle Schalemberg Diehl; Carlos Alberto Agnolin; Vinicius Felipe Bratz; Priscila Flôres Aguirre; Caroline Paim Sauter (Acta Scientiarum. Animal Sciences, 2017)
Current research evaluates productivity, stocking and nutritional rates of three forage systems with Elephant Grass (EG) + Italian Ryegrass (IR) + Spontaneous Growth Species (SGS), without forage legumes; EG + IR + SGS + Forage Peanut (FP), mixed with FP; and EG + IR + SGS + Red Clover (RC), mixed with RC, in rotational grazing method by lactating cows. IR developed between rows of EG. FP was maintained, whilst RC was sow to respective forage systems. The experimental design was completely randomized, with three treatments and two replication, subdivided into parcels over time. Mean rate for forage yield and average stocking rate were 10.6, 11.6 and 14.4 t ha-1; 3.0, 2.8 and 3.1 animal unit ha-1 day-1, for the respective systems. Levels of crude protein and total digestible nutrients were 17.8, 18.7 and 17.5%; 66.5, 66.8 and 64.8%, for the respective forage systems. The presence of RC results in better and higher forage yield in the mixture, whilst FP results in greater control of SGS. The inclusion of forage legumes in pasture systems provides better nutritional rates.